2001
DOI: 10.1006/anbe.2001.1848
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of reproduction among queens in the Argentine ant, Linepithema humile

Abstract: We investigated how queens share parentage (skew) in the Argentine ant, Linepithema humile, a social insect with multiple queens (polygyny). Overall, maternity of 546 male and female sexuals that mated successfully was determined with microsatellites in 26 colonies consisting of two queens and workers. The first main finding was that queens all contributed to sexual production. However, there was a significant departure from equal contribution to male and female sexual production in a notable proportion of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…The distribution of sucrose to queens varied greatly, with some queens receiving substantially more food than others. This finding suggests a possible reproductive dominance hierarchy, often observed in polygynous ant species (Fournier and Keller, 2001;Vargo, 1990). The larvae received relatively small amounts of sucrose with some individuals receiving substantially more food than others.…”
Section: Discussionmentioning
confidence: 79%
“…The distribution of sucrose to queens varied greatly, with some queens receiving substantially more food than others. This finding suggests a possible reproductive dominance hierarchy, often observed in polygynous ant species (Fournier and Keller, 2001;Vargo, 1990). The larvae received relatively small amounts of sucrose with some individuals receiving substantially more food than others.…”
Section: Discussionmentioning
confidence: 79%
“…The assumptions of single mating and equal share of worker production are supported by previous studies Krieger and Keller 2000;Fournier and Keller 2001). When the Hardy-Weinberg test rejected the assumption of random mating, the direct estimate of worker relatedness (r) was replaced by the estimator r* (''inbreeding corrected relatedness''; (Pamilo 1985) which corrects for the inflating effect of genetic substructuring of the reference population (see above).…”
Section: Statistical Analysesmentioning
confidence: 93%
“…Contrary to our third assumption, we found that coexisting L. acervorum queens exhibited significant variation in their relative contributions to female and male progeny (cf. Fournier and Keller 2001). In general, skew among male progeny was higher than among female progeny (B=0.56 and 0.15 among males and new workers, figure) and number of old (adult) workers (representing a measure of productivity; lower figure) respectively, and B adj =0.67 and 0.28 among males and new workers, respectively; data from five colonies in Table 3), from which it follows that skew among sexual progeny as a whole would be higher than skew estimated among females only.…”
Section: Discussionmentioning
confidence: 99%